2008
DOI: 10.2174/187152508785909474
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-Induced Cardiotoxicity

Abstract: The anthracyclines constitute a group of drugs widely used for the treatment of a variety of human tumors. However, the development of irreversible cardiotoxicity has limited their use. Anthracycline-induced cardiotoxicity can persist for years with no clinical symptoms. However, its prognosis becomes poor after the development of overt heart failure, possibly even worse than ischemic or idiopathic dilated cardiomyopathies. Due to the successful action of anthracyclines as chemotherapic agents, several strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 59 publications
1
119
0
2
Order By: Relevance
“…Also it was observed that the serum levels of transaminases, phosphatase and bilirubin went upto the levels grade 3 & 4 toxicities whereas the hepatomegaly did not progress beyond grade 2 in any of the patient till 6 th cycle. The increase in liver damage and subsequent release & increase of serum hepatic biomarkers may be due to the free radical generation by the chempotherapeutics during their metabolism in the liver (Ferreira et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Also it was observed that the serum levels of transaminases, phosphatase and bilirubin went upto the levels grade 3 & 4 toxicities whereas the hepatomegaly did not progress beyond grade 2 in any of the patient till 6 th cycle. The increase in liver damage and subsequent release & increase of serum hepatic biomarkers may be due to the free radical generation by the chempotherapeutics during their metabolism in the liver (Ferreira et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Although the pathogenesis of epirubicin-induced cardiotoxicity remains controversial, the oxidative stress-based hypothesis has gained the widest acceptance. [10] Robust generation of ROS is defined as oxidative stress, and significant increases in generation of ROS (a collective name for hydrogen peroxide, superoxide, and hydroxyl radicals) in cardiomyocytes, as well as serum concentrations, have been reported in epirubicin-induced cardiotoxicity. [10,11] ROS are excessively generated from a likely mitochondrial source, then hasten lipid peroxidation and DNA damage, and consequently initiate cell apoptosis or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Robust generation of ROS is defined as oxidative stress, and significant increases in generation of ROS (a collective name for hydrogen peroxide, superoxide, and hydroxyl radicals) in cardiomyocytes, as well as serum concentrations, have been reported in epirubicin-induced cardiotoxicity. [10,11] ROS are excessively generated from a likely mitochondrial source, then hasten lipid peroxidation and DNA damage, and consequently initiate cell apoptosis or necrosis. [12,13] Accordingly, successful antioxidant interventions targeted to reduce ROS offer insights into preventing epirubicin-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiotoxicity is the main drawback of anthracycline, which restraints more effective application of this drug to liver cancer patients (Ferreira et al, 2008). Myocardial degeneration is the most commonly encountered side-effects of anthracycline (Combs & Acosta, 1990).…”
Section: Discussionmentioning
confidence: 99%